Genetic variations in GBA1 and LRRK2 genes: Biochemical and clinical consequences in Parkinson disease - Smith, Laura J.; Lee, Chiao-Yin; Menozzi, Elisa; Schapira, Anthony H. V. (Frontiers in Neurology, 2022)
Variants in the GBA1 and LRRK2 genes are the most common genetic risk factors associated with Parkinson disease (PD). Both genes are associated with lysosomal and autophagic pathways, with the GBA1 gene encoding for the lysosomal enzyme, glucocerebrosidase (GCase) and the LRRK2 gene encoding for the leucine-rich repeat kinase 2 enzyme. GBA1-associated PD is characterised by earlier age at onset and more severe non-motor symptoms compared to sporadic PD. Mutations in the GBA1 gene can be stratified into severe, mild and risk variants depending on the clinical presentation of disease. Both a loss- and gain- of function hypothesis has been proposed for GBA1 variants and the functional consequences associated with each variant is often linked to mutation severity. On the other hand, LRRK2-associated PD is similar to sporadic PD, but with a more benign disease course. Mutations in the LRRK2 gene occur in several structural domains and affect phosphorylation of GTPases. Biochemical studies suggest a possible convergence of GBA1 and LRRK2 pathways, with double mutant carriers showing a milder phenotype compared to GBA1-associated PD. This review compares GBA1 and LRRK2-associated PD, and highlights possible genotype-phenotype associations for GBA1 and LRRK2 separately, based on biochemical consequences of single variants.